Utilization of the YouTube Platform as a Distance Learning Media to Improve Mathematical Problem-Solving Ability in Elementary School - Kurniawan, Ervin Dwi; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Jurnal Abdimas Kartika Wijayakusuma, 2022)
The ability of students to learn mathematics, especially in solving mathematical problems, is quite low. The pandemic conditions forced distance learning so that it hampered the improvement of students' ability to solve mathematical problems and non-mathematical problems. Innovation in learning is needed to help students to always be motivated in learning mathematics. This study aims to determine how much benefit the YouTube platform is as a distance learning medium to improve students' ability to solve problems mathematically. This activity method uses a quantitative approach with the target of grade 5 elementary school students. The results showed that the post-test average of students was 83.4%, an increase of 25.9% from the pre-test results which only reached 57.5%. This shows that videos uploaded to the YouTube platform can be an effective and innovative way to improve the mathematical problem-solving abilities of elementary school students.